Flutter Web - Build a Diary Web App with Flutter and Cloud Firestore - Dichone, Paulo (Packt Publishing, 2021)
Build adaptive web apps using a single code base About This Video Build a full-fledged, more complex, Flutter web app with Firestore, FirebaseAuth as the backend Create, authenticate, and log in users using Google Cloud FirebaseAuth Learn how to implement basic and advanced routing in Flutter 2.0 web In Detail If you have wondered how to leverage your pre-existing Flutter/Dart development skills, then you will be happy to know you can now build dynamic, scalable, and adaptive web apps with Flutter! Flutter 2.0 is a big release - you can use Flutter and Dart to build adaptive web and desktop apps - all with a single codebase. In this course, you will learn how to leverage Flutter (Web) 2.0 and Dart and build a capstone app called DiaryBook. In this course, you will build a full-fledged, more complex, Flutter web app with Firestore; FirebaseAuth as the backend; create, authenticate, and log in users using Google Cloud FirebaseAuth; create, edit, delete, update diary entries with Cloud Firestore backend; use providers, StreamBuilders in Flutter web; learn how to implement basic and advanced routing in Flutter 2.0 web; finally, deploy Flutter web app to firebase hosting. By the end of this course, you will have all the tools and knowledge you will need to build adaptive Flutter web apps competently and easily port the same app into desktop apps on your own! Who this book is for This course is designed for beginner to intermediate Flutter developers. Web developers who want to learn to build Flutter web apps and curious students who want to build their own Flutter web apps, iOS, Android, and desktop apps with Flutter 2.0 can also benefit from this course. Having some basic programming experience, in general, is helpful. If you have basic OOP (Object-Oriented Programming) concepts, you should be fine. Also, pre-existing Flutter and Dart programming experience or web development basics are helpful.